Oridonin: A Review of Its Pharmacology, Pharmacokinetics and Toxicity - Li, Xiang; Zhang, Chuan-Tao; Ma, Wei; Xie, Xin; Huang, Qun (Frontiers in Pharmacology, 2021)
Oridonin, as a natural terpenoids found in traditional Chinese herbal medicines Isodon rubescens (Hemsl.) H.Hara, is widely present in numerous Chinese medicine preparations. The purpose of this review focuses on providing the latest and comprehensive information on the pharmacology, pharmacokinetics and toxicity of oridonin, to excavate the therapeutic potential and explore promising ways to balance toxicity and efficacy of this natural compound. Information concerning oridonin was systematically collected from the authoritative internet database of PubMed, Elsevier, Web of Science, Wiley Online Library and Europe PMC applying a combination of keywords involving “pharmacology”, “pharmacokinetics” and “toxicology”. New evidence shows that oridonin possesses a wide range of pharmacological properties, including anticancer, anti-inflammatory, hepatorenal activities as well as cardioprotective protective activities and so on. Although significant advancement has been witnessed in this field, some basic and intricate issues still exist such as the specific mechanism of oridonin against related diseases not being clear. Moreover, several lines of evidence indicated that oridonin may exhibit adverse effects, even toxicity under specific circumstances, which sparked intense debate and concern about security of oridonin. Based on the current progress, future research directions should emphasize on 1) investigating the interrelationship between concentration and pharmacological effects as well as toxicity, 2) reducing pharmacological toxicity, and 3) modifying the structure of oridonin—one of the pivotal approaches to strengthen pharmacological activity and bioavailability. We hope that this review can provide some inspiration for the research of oridonin in the future.